The effect of fasting on the interaction between taste perception and metabolic regulation : a thesis presented in partial fulfilment of the requirements for the degree of Master of Food Technology at Massey University - Li, Wenjing (Massey University, 2012)
Taste perception, via reception of tastants and endocrine signalling within the tongue, plays a key role in consumer acceptance and sensory evaluation of foods. Taste perception triggers hormones that are crucial in the control energy balance and appetite exerts a strong effect on food intake, satiety and metabolic regulation. Due to the complex interaction of genetic, biological and psychological factors, the influence of fasting on the relationship between taste perception and associated metabolic parameters remains to be explored. The present study investigated the effect of fasting on interaction between taste perception and metabolic regulation through three main objectives. The first objective was to explore the relationship between the bitter taste sensitivity and the fatty acid taste sensitivity. Forty healthy male adults were classified into three taster groups based on their sensitivity to bitter agent 6-N-2-propylthiouracil (PROP): nontasters (n=10), medium tasters (n=20) and supertasters (n=10). The groups were also confirmed with fungiform papillae densities. However, no significant correlation was observed between PROP status and fungiform papillae densities. Also, results showed neither PROP status nor the fungiform papillae density associated with fatty acid thresholds. The second objective was to investigate the effect of overnight fasting or meal consumption on sweet and fatty acid taste perception. Detection thresholds for sucrose and linoleic acid were measured by using ASTM method during fasted and satiated state. The result showed increases in sucrose detection thresholds under the both fasted state and satiated state. The linoleic acid thresholds increased after meal consumption and reduced after prolonged fasting. This led to a further investigation on the last objective- the role of key plasma metabolites on fatty acid taste perception in fasting and satiated states. The results indicated that neither the effect of metabolic status on fatty acids thresholds nor relationships between fatty acid thresholds and blood metabolic parameters were observed. Furthermore, there was no significant difference in blood metabolites across PROP taster group, which means that PROP classification cannot be considered as a predictor to the blood metabolites. In conclusion, the present study provides evidence suggesting that PROP sensitivity cannot predict fatty acid taste sensitivity and metabolic status has no effect on fat taste perception. In addition, blood metabolites do not show any difference among PROP taster group and any relationship with taste perception either.
Keywords: Taste perception; Sensory evaluation; Food tasting; Fasting